Design of High-Throughput Superoleophobic Copper Meshes for Oil-Water Separation. Issue 1745 (9th June 2015) - Liu, HaoRan; Jia, BoKang; Li, GuanQiu; Nooralla, Sumaya; Zhang, TieJun
ABSTRACT: Advanced materials with desired wettability are extremely important for environmental sustainability, such as oily industrial wastewater treatment and oil spill cleanup. To meet this demand, a scalable nanoengineering approach was developed to fabricate superhydrophilic and underwater superoleophobic inorganic meshes for cross-flow filtration and oil/water separation. The resulting nanostructured copper meshes exhibit superhydrophilicity and underwater superoleophobicity (oil contact angle approaching to 159°). With these meshes, very high values of filtration flux (≥900, 000 Lh -1 m -2 ) have been achieved, with ultra-low oil residue in the filtrate (<40 ppm) and long water retention time (more than 1 h). The proposed nanoengineering method paves the way for effective gravity-driven separation of immiscible oil/water mixtures, especially for low-density oil purification.